Primary enuresis and comorbid sleepwalking in an adolescent: Diagnostic and therapeutic challenges, a case report from rural Nepal - Sah, Alok Kumar; Subedi, Rashmi; Rawal, Nabin; Bhandari, Jeetendra (Journal of Karnali Academy of Health Sciences, 2026)
Primary nocturnal enuresis (PNE) and somnambulism are categorized as arousal disorders resulting from non-rapid eye movement (NREM) sleep. These diseases have a shared neurophysiological basis: poor arousal from slow-wave sleep. We report a case of a 10-year and 11-month-old male who presented to a tertiary care hospital in Karnali Academy of Health Sciences, Jumla, Nepal, with persistent enuresis and concurrent sleepwalking. Further, evaluation indicated a 2 to 3-year history of intermittent somnambulism. This instance emphasizes the importance of viewing enuresis as part of a broader context of arousal disorders rather than as a standalone urological issue. It also emphasizes the difficulties of handling such situations in resource-constrained environments, as well as the importance of integrating behavioral and neurophysiological techniques. The initial pharmacological therapy with imipramine (25 mg at bedtime) produced a response to symptom frequency.